Morfologiniai lietuvių, norvegų ir suomių kalbų kauzatyvai - Rackevičienė, Sigita (Kalbotyra, 2002)
The aim of the article is to provide an analysis and comparison of the formal structure of the morphological causatives (causative verbs) in Lithuanian, Norwegian and Finnish. Morphological causatives of these languages are grouped into three types: (a) causatives with an affixal marker of causation, (b) causatives with an apophonic marker of causation, (c) causatives without an overt marker of causation. The findings of the analysis lead to the following conclusions: 1) In Lithuanian and Finnish, the main type of morphological causatives is causatives with an affixal marker of causation, e.g. Lith. šokdinti ‘to have sb. dance’; Fin. tansittaa ‘to have sb. dance’. In Norwegian, on the other hand, the main type of morphological causatives is causatives without an overt marker of causation that form oppositional pairs with intransitive verbs, e.g. begynne ‘begin; begin sth’. 2) Lithuanian and Norwegian have morphological causatives with an apophonic marker of causation, e.g. Lith. kilti : kelti ‘rise: raise’, Norw. fare : føre ‘go somewhere : take sb. somewhere’. Such causatives are not found in Finnish as Finno-Ugric languages are not characterized by root-vowel change. 3) In all three languages, a tendency of losing an overt marker of causation can be noticed. In Lithuanian, affixal causatives derived from transitive verbs (curatives) are often replaced by basic transitive verbs, e.g. siūdintis paltą ‘to have one’s coat made’, siūtis paltą ‘to make one’s coat; to have one’s coat made’. In Finnish, this tendency can be noticed as well, though Finnish curatives are still used actively. The number of Norwegian morphological causatives without an overt marker is increased by some Norwegian non-causative verbs which are already beginning to be used with one more – causative – meaning, e.g. stilne ‘calm down; to have sb. calm down’; farge håret ‘to dye your hair yourself; to have your hair dyed’. These tendencies show that certain meanings, clear from the context and social relations, tend to be simplified.